Research in practice: Terre Blanche, M and Durrheim, K (eds) (1999) Research in practice: Applied methods for the social sciences Cape Town: UCT Press ISBN 1-919713-35-2 pbk. 511 pages. - Parker, Ian (PINS-Psychology in Society, 2026)
This marvellous book performs a double subversion of ·methodology" for psychology students. First of all the book is a counterweight to the hegemony of US American psychology and its imitators in Europe. One of the little cracker quotes in the margin reminds us, for example, that the US Defence Department employs more psychologists than any other company or organisation in the world (p198). It is very difficult to find psychology textbooks that are not saturated with US American values and advertisements for particular culturally-specific kinds of psychology and psychopathology Research In practice, then, ensures that the usual US publisher’s ruse of binding in some extra pages about the part of the world it hopes to peddle its wares to is thoroughly addressed. In this book we have hundreds of examples specifically about South Africa, ranging from the discussions of representation (of atlas projections of the world in which the size of Africa is diminished or emphasised) to arguments about how representations are made (of experiences of health among mineworkers in Carletonville). There is a deliberate localisation of research concerns, and so the concerns of South African students are hooked all the way through.